2019
DOI: 10.3390/su11123405
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Baltic Sea Action Plan (BSAP) Using the OECD Principles on Water Governance

Abstract: This paper uses the Organization for Economic Co-operation and Development (OECD) water governance principles to assess the governance of the implementation of the Baltic Sea Action Plan (BSAP), with a focus on the eutrophication segment. Whilst governance assessments can be used as auditing functions, this study was done with the goal of stimulating reflection, in order to investigate whether the governance systems have made any improvements. This is especially needed, since the BSAP is to be renewed in 2021,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…There were originally (1987-1991) 43 Areas of Concern, with 5 common ones, 26 in the United States and 17 in Canada. To date there are four hot spots delisted, or fully recovered, in Canada and four in the United States [6]. In the Baltic Sea Region, significantly polluted sites, HELCOM Hot spots (established in 1992) remain, as three quarters (121 out of 162) have been cleaned up as of June 2019 [18].…”
Section: Take Care Of Hotspotsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were originally (1987-1991) 43 Areas of Concern, with 5 common ones, 26 in the United States and 17 in Canada. To date there are four hot spots delisted, or fully recovered, in Canada and four in the United States [6]. In the Baltic Sea Region, significantly polluted sites, HELCOM Hot spots (established in 1992) remain, as three quarters (121 out of 162) have been cleaned up as of June 2019 [18].…”
Section: Take Care Of Hotspotsmentioning
confidence: 99%
“…Similarly, evaluations of key Great Lakes institutions, such as the International Joint Commission, the Great Lakes Commission, the Great Lakes St. Lawrence Cities Initiative, the Great Lakes Fishery Commission, and the Binational Executive Committee, can provide valuable insights for adaptive governance of the Great Lakes. In the Baltic Sea Region, institutional accountability can help in decreasing governance gaps, such as stakeholder participation, funding deficits and governance tradeoffs [6].…”
Section: Institutional Accountabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research has found that the ecosystem approach has the potential to improve HELCOM's adaptive capacity [11]. In the case of HELCOM, the analysis of the institutional change following the efforts to apply the ecosystem approach is especially pertinent at a time when review of the BSAP implementation indicates that implementation actions are lagging behind the desired status [12,13]. It is also relevant as it can inform the dialogue on the update of the BSAP that will be announced in 2021.…”
Section: Introductionmentioning
confidence: 99%